The Awareness level of Students of the Education College in the State of Kuwait about the Digital Citizenship Dimensions - Al-Rashidi, Abdulaziz Mutlaq Saad Al-Watari; Al-Mutawa, Farah Abdulaziz (Journal of Educational and Psychological Sciences, 2024)
The study aimed to identify the Awareness level of Students of the Education College in the State of Kuwait About the Digital Citizenship Dimensions and its relationship to the variables (gender, year of study, specialization). Male and female students of the College of Education in the State of Kuwait, whose number was 602, were selected in a simple random way, and after verifying the validity and reliability of the questionnaire and collecting data and analyzing them with appropriate statistical methods using the SPSS program, the study concluded that the awareness level of male and female students of the Education College at Kuwait University about the digital citizenship dimensions came With a high degree, with an arithmetic mean (4.27), the study also showed that there were no statistically significant differences in the estimates of the sample members due to the gender variable, and the study also showed that there were no statistically significant differences in the estimates of the sample members due to the specialization variable. The variable of the year of study is attributed to the axis of digital access in favor of the fourth and fifth academic year compared to the first and third academic year, as well as the axis of rights and responsibilities. The study included a set of recommendations and proposals.